Strategi dan Tantangan Pengembangan Berpikir Reflektif dalam Pembelajaran IPA Sekolah Dasar - Desky, Rizkyu Ardityan; Fatmawati, Siti Nur; Kastur, Annita; Mustain, Mustain; Julianto, Julianto; Rukmi, Asri Susetyo (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2025)
The development of reflective thinking in science learning at the elementary school level still faces various challenges. Many teachers have not fully understood the appropriate approaches and strategies to encourage students to reflect on their thinking processes and learning outcomes. A dense curriculum, limited time, and the lack of professional training are among the inhibiting factors for integrating reflective thinking skills into teaching practices. This study aims to examine effective strategies for developing reflective thinking in science learning at elementary schools, as well as the challenges in its implementation. A descriptive qualitative method was used, with data collection conducted at three elementary schools in Surabaya, involving sixth-grade students and classroom teachers. The findings indicate that the main challenges in developing reflective thinking include time constraints, teachers’ lack of experience, inadequate facilities and infrastructure, and students’ habits that prioritize memorization. Strategies that can be applied to address these challenges include integrating reflective activities into lessons, providing teacher training, and ensuring the availability of supporting facilities. The successful development of reflective thinking skills requires support from schools and educational policies. It is expected that, through the implementation of appropriate strategies, students’ reflective thinking abilities can be optimally developed to support meaningful learning.